Ionizing Radiation, Antioxidant Response and Oxidative Damage: Radiomodulators - Elena Obrador; Alegría Montoro (MDPI AG, 2023)
Ionizing radiation (IR) is the energy released by atoms in the form of electromagnetic waves (e [...]